Effect of the operating temperature on thermal EHL performance of steel-POM gears - ZHOU Jia’ao; LIU Xiaoling; ZHANG Zheng; LI Qun (Jixie chuandong)
ObjectiveThe temperature significantly influences the elastic modulus of polymer gears, which consequently affects their elastohydrodynamic lubrication performance. It is therefore imperative to investigate the impact of temperature on the lubrication characteristics of polymer gears.MethodsA thermal elastohydrodynamic lubrication (TEHL) model for steel-POM gear pairs was developed, incorporating temperature-dependent variations in the elastic modulus of polyformaldehyde (POM) gears. The multigrid technique and the column scanning method were employed to systematically analyze and discuss the TEHL performance of steel-POM gear pairs under diverse operating temperatures.ResultsThe results show that the friction coefficient of the steel-POM gear decreases forward of the pitch point and increases afterward of the pitch point. The maximum temperature of the oil film of the steel-POM gear is near the polymer gear. The inlet viscosity has a great influence on the oil film thickness, and the elastic modulus is the major factor for the oil film pressure. The oil film temperature is greatly determined by the environmental viscosity, and the oil film pressure caused by the elastic modulus has little effect. As the operating temperature increases, the friction coefficient decreases.